Effectiveness of a nursing psychoeducative intervention as a helping tool in children´s mourning work - Maria del Carmen Pérez González (Fundación para el Desarrollo de la Enfermería, 2009)
The children grief has many special characteristics determinated by the childhood features. Several studies consider that children may have anxiety reactions, fears, depression and disadaptated behaviour when a relative is fort.The objective of this study is to know the effectiveness of a psychoeducative intervention of a Primary Care nurse in preventing misadaptative behaviours related to grief in children.To achieve this objective, a randomized controlled trial with an experimental group and a control group has been designed. 198 children and teenagers will be included in it (there will be randomized assigned 98 on each group) from 5 to16 years old, having been affected of a relating grief, belonging to the Primary Care Centers of the 9, 10 and 11 areas in Madrid Community. Children and teenagers included in the experimental group will take a psychoeducative intervention based on 7 individualized weekly sessions. Measures of the punctuations obtained on the Children Behaviour Test will be made when children will be included in the study and after 3, 6 and 12 months.